Research Progress in Isolation and Enrichment of Fetal Cells from Maternal Blood - Ying Tang; Qiaojin Tang; Haiyan Luo; Xuehui Zhang; Qiuyu Chen; Wenying Tang; Ting Wang; Lihua Yang; Hongwu Liao (Journal of Chemistry)
Prenatal diagnosis is an important means of early diagnosis of genetic diseases, which can effectively reduce the risk of birth defects. Free fetal cells, as a carrier of intact fetal genetic material, provide hope for the development of high-sensitivity and high-accuracy prenatal diagnosis technology. However, the number of fetal cells is small and it is difficult to apply clinically. In recent years, noninvasive prenatal diagnosis (NIPD) technology for fetal genetic material in maternal peripheral blood has developed rapidly, which makes it possible to diagnose genetic diseases by fetal cells in maternal peripheral blood. This article reviewed the current status of fetal cell separation and enrichment technology and its application in noninvasive prenatal diagnosis technology.